Dynamic Positioning System Design for A Marine Vessel with Unknown Dynamics Subject to External Disturbances Including Wave Effect - Hosseinnajad, Alireza; Loueipour, Mehdi (China ocean engineering, 2020)
In this paper, a new control system is proposed for dynamic positioning (DP) of marine vessels with unknown dynamics and subject to external disturbances. The control system is composed of a substructure for wave filtering and state estimation together with a nonlinear PD-type controller. For wave filtering and state estimation, a cascade combination of a modified notch filter and an estimation stage is considered. In estimation stage, a modified extended-state observer (ESO) is proposed to estimate vessel velocities and unknown dynamics. The main advantage of the proposed method is its robustness to model uncertainties and external disturbances and it does not require prior knowledge of vessel model parameters. Besides, the stability of the cascade structure is analyzed and input to state stability (ISS) is guaranteed. Later on, a nonlinear PD-type controller with feedforward of filtered estimated dynamics is utilized. Detailed stability analyses are presented for the closed-loop DP control system and global uniform ultimate boundedness is proved using large scale systems method. Simulations are conducted to evaluate the performance of the proposed method for wave filtering and state estimation and comparisons are made with two conventional methods in terms of estimation accuracy and the presence of uncertainties. Besides, comparisons are made in closed-loop control system to demonstrate the performance of the proposed method compared with conventional methods. The proposed control system results in better performance in the presence of uncertainties, external disturbance and even in transients when the vessel is subjected to sudden changes in environmental disturbances.